DFSP of the Breast: Histomorphological, Immunohistochemical, and Molecular Features of a Rare Case in an Unusual Location. Issue 8 (19th September 2021) - Laharwani, Hansini; Prakash, Varsha; Walley, Debbie; Akhtar, Israh
Abstract : We present a case of a 21-year-old female with a vague nontender mass in the lower inner quadrant of the left breast discovered incidentally on chest imaging following trauma. A breast ultrasound demonstrated an 8×6×8 mm irregular hyperechoic mass at the 7 o'clock position of the left breast, 9 cm from the nipple. The mass was graded Breast Imaging Reporting and Data System (BI-RADS) category 4 (suspicious finding). An ultrasound-guided biopsy of the mass showed a proliferation of monotonous spindled cells in a storiform pattern with tapered nuclei with infiltration into the adipose tissue. No normal breast elements were identified in the biopsy. Myofibroblastoma was the first differential diagnosis; however, the characteristic infiltrative pattern of the tumor mandated additional tests including fluorescence in situ hybridization to rule out a dermatofibrosarcoma protruberance (DFSP). Immunohistochemical staining showed positive staining for CD34, which can be positive in myofibroblastoma also. However, fluorescence in situ hybridization demonstrated a platelet-derived growth factor B (22q13.1) gene rearrangement confirming a diagnosis of DFSP. The patient underwent a wide local excision of the DFSP for definitive treatment. She is doing well with no recurrence reported so far, after 15 months of follow-up. Conventional DFSP does not metastasize but is prone to recurrence making wide margins imperative for definitive treatment.